Analysis of Public Behavior Regarding Food Waste - Alip Suroto (An International Journal Tourism and Community Review, 2024)
In this study, bibliometric analysis using VOSviewer and Publish or Perish was employed to identify dominant trends in the analysis of community behaviors related to food waste. The analysis results indicate an increasing interest among researchers in understanding and addressing the social, cultural, and psychological factors influencing food waste behaviors within communities. There has been a paradigm shift in research emphasis from individual factors towards a more comprehensive understanding of the social and cultural contexts that affect food waste behaviors. This research focuses more on developing effective and sustainable food waste reduction strategies at the community level through promoting supportive policies, public education, social campaigns, and participatory approaches. In conclusion, this study contributes significantly to understanding the dominant trends in community behavior analysis related to food waste. The findings provide valuable insights for researchers and practitioners in further research development and assist in formulating policies and strategies for more effective community-level interventions against food waste, with a focus on the social and cultural factors influencing food waste behaviors.